ANALISIS PENAWARAN KEDELAI DI KABUPATEN GROBOGAN - Suprapti Suprapti; Sri Marwanti; Umi Barokah (Caraka Tani: Journal of Sustainable Agriculture, 2011)
Soybean crop area that is unstable causing the production of soybean in the District Grobogan as one of the centers in Central Java soybean fluctuated sharply. This study aims to 1) Review and analyze the factors that affect soybean supply in the District Grobogan and 2) Review and analyze the elasticity of supply in the District Grobogan soybean due to changes in the factors that influence it. He method used in this research is descriptive method. Determination of the study area is done by purposive technique with consideration of the area has the largest soybean yield compared to other districts, namely Grobogan district with 15,71 quintal per hectare productivity. Results of secondary data analysis states that the supply function model of soybean in the District Grobogan is Qt = bo + 13,544 Pt-1 to 0,098 Qt-1 + 1,404 At – Purea 24,119 – 3,077 + 7,191 Wt PSP36 with coefficient of determination 0,891 Calculated F value obtained at 15,030, which means that the variable price of soybeans a year earlier, the amount of soybean production last year, the total area harvested during the year, the price of urea fertilizer, the price of SP 36 on the year.